(untitled) (Journal of the Asiatic Society of Bangladesh, Science, 2017)
The present article focuses the status of angiosperm flora of Sreenagar upazila under Munshiganj district. The study was done from July 2015 to June 2016. A total of 219 plant species of angiosperms was identified belonging to 165 genera and 70 families. Among them 38 species were monocotyledons and 181 plant species were dicotyledons. Herbs were the largest life forms among the angiosperms and contained about 58% of total plant species occurring in this area. Trees and shrubs occupied 23% and 12% respectively. Climbers were 6% but epiphytes (1%) were very negligible in number in the study area. About 51 medicinal plants were recorded from this study. The following species viz. Lasia spinosa, Calamus tenuis, Tinospora crispa, Passiflora foetida and Calotropis procera were recorded only once and hence considered as rare species in Sreenagar upazila. An invasive poisonous plant Parthenium hysterophorus was also found in Sreenagar. Asiat. Soc. Bangladesh, Sci. 43(2): 161-172, December 2017